(untitled) (Geographical Journal of Nepal, 2018)
Physicochemical property of top layer of soil is very important for plant growth having life supporting agriculture production, forestry and environmental sustainability. Soil texture and its chemical properties are determined by various factors inversely soil property determines productivity for them. This study was conducted in Jita and Taksar area of Lamjung district of Nepal. Soil samples were collected from the field. Coarse fragments, soil texture and pH were measured from soil samples. Properties of soil were analyzed by mechanical and chemical methods such as sieve, hydrometer and digital pH meter. Dominant soil textural class is loam followed by silt loam. Higher proportion of sand is found in higher elevation and steeper slope. Inverse relationship is found of silt. Dominant soil is found to be slightly to moderately acidic. Soil pH level decreases with increasing altitude and slope gradient. Cultivated land is less acidic than other land cover category. It is found that lower elevation and lower slope gradient have more proportion of coarse fragments. Chi-square test proves the significant difference of pH, soil texture class, soil particle size and coarse fragment at different elevation, slope gradient and land use. However, variation of sand at different slope gradient and land use is not explained well. The Geographical Journal of Nepal Vol. 11: 45-62, 2018